Macunaíma, de Mário de Andrade : uma leitura em face da teoria crítica de Walter Benjamin - Deleprani, Felício Oscar (2024)
This research aims to address the following research question: to what extent does Mário de Andrade's work Macunaíma: o herói sem nenhum caráter incorporate the experience (Erfahrung) mentioned by Walter Benjamin in the essay The Storyteller: considerations about the work of Nikolai Leskov. In an attempt to answer this question, the main objective was established as the analysis of the Mário de Andrade's rhapsody in the context of Walter Benjamin's critical theory. Methodologically, three specific stages were delineated for the research. The first involved a survey in the Biblioteca Nacional de Teses e Dissertações (BDTD) database to understand the current state of research addressing the connections between Mário de Andrade and Walter Benjamin. In the second stage, detailed in the second chapter of the dissertation, the aim was to establish elective affinities between the two authors based on their readings of figures such as Sigmund Freud and Charles Baudelaire. Lastly, in the third stage, the objective was to extract the analytical categories present in The Storyteller: considerations about the work of Nikolai Leskov and conduct an analytical reading of Macunaíma in light of these categories. The finds indicate that the analyzed rhapsody incorporates, as a condition for the elaboration of experience (Erfahrung), "orality" (Mündlich), narrative rooted in the "people" (Volk), "tedium" (Langeweile), and the "art of giving advice" (Rat Geben). These results suggest that in Macunaíma, Mário de Andrade seeks an immersion in Brazil's pre-industrial era to incorporate this experience (Erfahrung) into the 20th-century modernist aesthetic. This updating expands the understanding of the impact that Mário de Andrade's literary work had on the formation of the Brazilian people's identity